Determination of Trace Elements in Cow Placenta by Tungsten Coil Atomic Emission Spectrometry - Gonçalves, Daniel A.; Soncin, Ana C. [UNESP]; Donati, George L.; dos Santos, Mirian C. [UNESP] (Springer Nature, 2017)
Tungsten coil atomic emission spectrometry (WCAES) is used to determine trace levels of Mn (403.1 nm) and Cr (425.5 nm) in cow placenta. All samples were collected in Ilha Solteira, SP, Brazil. The instrumental setup is based on a tungsten filament extracted from 150 W, 15 V microscope light bulbs, a solid state power supply, fused silica lens, crossed Czerny-Turner spectrograph, and a thermoelectrically cooled charge-coupled device detector. The limits of detection (LOD) and quantification (LOQ) for Cr are 2 and 8 μg L−1, and 20 and 60 μg L−1 for Mn, respectively. Recoveries for 0.30 mg L−1 spikes of each analyte were in the range 93.0–103.0%, and relative standard deviation (RSD) was between 6.50 and 7.20% for both elements. Placenta samples were microwave-assisted digested with diluted HNO3 and H2O2 and analyzed by WCAES. The results for Cr and Mn were compared with values obtained by tandem inductively coupled plasma mass spectrometry (ICP-MS/MS). No statistically significant difference was observed between the different methods by applying a paired t test at a 95% confidence level. The average concentrations of Cr and Mn in the placentas evaluated were 0.95 ± 0.22 and 2.64 ± 0.39 μg g−1, respectively. By using a short integration time, LODs for Cr and Mn were lower than values reported by recent works using a similar WCAES system.
Keywords: Cow embryo; Micronutrients; Placentome; Trace analysis; Tungsten atomizer